PENGARUH SOSIALISASI DAN PENERAPAN E-FAKTUR TERHADAP TINGKAT PELAPORAN SPT MASA PPN - Suwarno, Suwarno (Sekolah Menengah Kejuruan (SMK) Pustek, 2018)
The purpose in this research is to determine whether there is influence between socialization and implementation of e-invoices to the VAT return period level reporting on a taxable entrepreneur tax service office pratama Depok Cimanggis. the model used in this research is quantitative analysis research model. The data used are primary data by spread out  questionnaires to the Taxable Entrepreneur contained in  KPP Pratama  Depok Cimanggis, the sampling technique using simple random sampling. Then the questionnaires were distributed to 94 respondents. Technical analysis of test data quality is test validity, reliability and classic assumption test and multiple linear regression test that is testing the coefficient of determination, t test and f. The results showed that the dissemination of e-invoices not have a significant impact on the level of reporting VAT return period, otherwise the implementation of e-invoicing positive and significant impact on the level of return period PPN. And reporting research results simultaneously (together) dissemination and application variables e-invoicing positive and significant impact on the level of reporting VAT return period